The Effect of Work Behavior, Leadership Style and Commitment on the Performance of Primary Employees of Police Cooperatives - Marsuhin Marsuhin (Mahameru Publisher, 2023)
This study aims to examine the influence of work behavior, leadership style, and commitment to employee performance. This study uses a quantitative approach. The samples used were 32 people who were employees of the Lumajang District Police Cooperative. The results of the study show that work behavior and commitment have a significant effect on employee performance. However, leadership style has no significant effect on employee performance. An important implication of this research is that it is very important for the organization to pay attention to the work behavior and commitment of its employees. Leadership style has no effect because it often changes leaders. So employees are familiar with various leadership styles in managing the organization.